The Art of Remediating Age-Related Cognitive Decline: Art Therapy Enhances Cognition and Increases Cortical Thickness in Mild Cognitive Impairment. - YU JUNHONG (Cambridge University Press (CUP), 2020)
10.1017/S1355617720000697